THU0591-HPR The Longitudinal Impact of Persistent Depression on Physical Health Outcomes in Rheumatoid Arthritis. (10th June 2014) - Matcham, F.; Norton, S.; Scott, D.L.; Steer, S.; Hotopf, M.
Abstract : Background: Depression is highly prevalent in RA and is associated with increased mortality, disability and healthcare costs [1, 2]. There is limited evidence assessing the longitudinal impact of depression on RA outcomes, particularly objectively-reported clinical outcomes. Objectives: To assess the impact of persistent depression on physical health outcomes over a 2-year follow-up period. Methods: A secondary data analysis of a clinical trial (CARDERA) was performed [3]. Depression and physical health outcomes were measured at baseline and 6-montly intervals for 2-years. Depression was measured using the EQ-5D, and patients were categorised into 4 groups: 1) never depressed; 2) depressed at <50% of time-points; 3) depressed at >50% of time-points; and 4) depressed at every time-point. Physical health outcomes were: Larsen score; tender joint count (TJC); swollen joint count (SJC); ESR; assessor and patient global assessments (AGA/PGA); HAQ; pain; and DAS-28. Results: Data was available for 379 patients. Patients' mean age was 54.1 (12.3), and 68.3% of the sample were female. In total, 25.9% were never depressed, 36.9% were depressed <50% of the time, 27.4% were depressed >50% of the time, and 15.8% were depressed at every time-point. Conclusions: Increasing persistence of depression over time tends to be associated with poor physical health outcomes, with discordance between subjectively and objectively measured outcomes. These findings have significant implications: mental health should be measured and monitored throughout the course of treatment [4]; DAS-28 scores may be inflated in depressed patients, which needs to be considered when making treatment decisions. References: Matcham F et al. The prevalence of depression in Rheumatoid Arthritis: A systematic review and meta-analysis. Rheumatology 2013; 52: 2136-48. Bruce T. Comorbid depression in rheumatoid arthritis: Pathophysiology and clinical implications. Current Psychiatry Reports 2008; 10: 258-64. Choy EHS et al. Factorial randomised controlled trial of glucocorticoids and combination disease modifying drugs in early rheumatoid arthritis. Ann Rheum Dis 2008; 67: 656-63. Rayner L et al. Embedding integrated mental health assessment and management in general hospital settings: feasibility, acceptability and the prevalence of common mental disorder. Gen Hosp Psychiatr (in press), doi: 10.1016/j.genhosppsych.2013.12.004. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2878